KONSEP POLA ASUH ISLAMI DALAM BUKU ILMU JIWA AGAMA ZAKIAH DARADJAT: RELEVANSINYA DALAM MENANGANI STIGMA KESEHATAN MENTAL DI ERA KONTEMPORER - Fa'iza; Marlina; Sholeh Hasan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mental health stigma remains a significant issue in the contemporary era, contributing to low public awareness and inadequate responses to mental health problems. As the primary environment for child development, the family plays an essential role in shaping children's perceptions of mental health through parenting practices. This study aims to analyze the concept of Islamic parenting presented in Zakiah Daradjat’s book Ilmu Jiwa Agama and examine its relevance in addressing mental health stigma in the contemporary era. This research employed a qualitative approach using library research. Primary data were obtained from Zakiah Daradjat’s Ilmu Jiwa Agama, while secondary data were collected from books, journals, articles, and other relevant scholarly works. Data were gathered through documentation and literature review and analyzed using content analysis. The findings indicate that Islamic parenting according to Zakiah Daradjat emphasizes affection, exemplary behavior, religious education, emotional security, and empathetic approaches in child-rearing. These principles are relevant to addressing mental health stigma by fostering emotional literacy, reducing judgmental attitudes toward individuals experiencing psychological problems, and strengthening mental resilience based on Islamic values. Therefore, Islamic parenting can serve as an effective approach to promoting mental well-being and reducing mental health stigma in contemporary society.